The Use of Graphic Organizer Focusing on Story Elements to Promote Students’ Narrative Writing - Wongsasawat, Rattanyu; Waewchimplee, Waewalee (ETERNAL (English Teaching Journal), 2025)
This study investigated the impact of using graphic organizers focusing on story elements to enhance the narrative writing ability of sixth-grade students. The research aimed to: (1) examine the effects of graphic organizers on students’ narrative writing abilities, (2) compare students' post-test narrative writing abilities with their pre-test performance, and (3) explore students' opinions on using graphic organizers during the writing process. A pre-experimental design with one group pre-test and post-test was employed, involving 30 sixth-grade students from Marie Kaengkhro School. The students participated in lessons integrating graphic organizers based on Matsuda and Hammill's writing principles. The results indicated a significant improvement in students' post-test scores across all narrative writing criteria, with gains in organization, idea development, and conventions. The paired t-test confirmed the statistical significance of the difference between pre- and post-test scores (t = 11.79, p < .001). Student feedback was overwhelmingly positive, with 95% reporting that the graphic organizers helped them organize their ideas and improve their narrative writing skills. The findings suggest that graphic organizers effectively enhance narrative writing skills, particularly in EFL contexts. Future research could explore the long-term effects of this approach across different educational settings.